Experimental Analysis of Mass Exchange Across a Heterogeneity Interface: Role of Counter‐Current Transport and Non‐Linear Diffusion. Issue 6 (16th June 2022) - Walczak, Monika S.; Erfani, Hamidreza; Karadimitriou, Nikolaos K.; Zarikos, Ioannis; Hassanizadeh, S. Majid; Niasar, Vahid
Abstract: Solute transport in heterogeneous and fractured systems is a complex process given the permeability contrasts and the time scales discrepancies of transport in high‐permeability versus low‐permeability regions. We studied this phenomenon by injecting a solute (dyed water) in a micromodel comprising a single channel in contact with a porous medium and evaluated the mass exchange across the interface between the channel and porous medium (resembling the interface between free flow and porous media regions). Two sets of transport experiments were performed at three injection rates of 0.01, 0.1, and 1 ml/hr. Injection of dyed water into a clean‐water‐filled micromodel (referred to as the loading process hereafter) and injection of clean water into a dyed‐water‐filled micromodel (referred to as the unloading process hereafter). The dynamics of solute transport was recorded using time‐lapse optical imaging. Our experimental results demonstrated the change of the mass exchange rate coefficient with time and a much smaller transfer rate coefficient during the unloading compared to the loading process. It is proposed that concentration‐dependent counter‐current advection‐diffusion cause slow‐down and further delay in the transport. These results may provide further explanation for the observed slow release of contamination in aquifers. Plain Language Summary: Solute transport in fractured aquifers is complex as the time scale of transport in fractures and matrix is very different. This study investigates how the mass exchange across a heterogeneity interface varies as a function of flow dynamics and the transport process. Detailed experimental analysis on a synthetic porous medium has been performed and the mass exchange has been quantified using the optical imaging of a tracer. Results can help better understanding the physics of the process and developing more physically based models which can assist the assessment of contaminant transport in fractured systems. Key Points: Mass exchange across a heterogeneity interface was quantified using optical imaging The linear mass exchange rate coefficient is non‐unique and process‐dependent Nonlinear diffusion and counter‐current transport slow down the unloading process